Formação para cuidadores de idosos: uma análise de propostas formativas - Câmara, Teresa Maria da Silva (2017)
The present study investigates the training of caregivers of the elderly who, in the current context, is in the level of initial and continued education, in the qualification of people, to exercise care for the elderly person. As a research problem, there is no proposition of curricular guidelines for training, because it is an occupation without professional regulation, whose qualification is done through courses, without standardization of contents and training processes. The aim of this dissertation is to develop a diagnostic study on the development of training proposals for caregivers of the elderly in a public and private institution in the state of Ceará, with the aim of proposing a thematic matrix that will comprehensively address aspects relevant to the exercise of care To the elderly. The objective of this study is to analyze the legal and pedagogical documents that guide the organization of the training of Elderly Caregivers, in the institutional scope; To identify the perceptions of coordinators and teachers about the training proposals for Elderly Caregivers, regarding the training in which they are involved; To describe the Political Pedagogical proposals of the training courses for Elderly Caregivers, identifying the nature of this formation and elaborate a thematic matrix that guides the organization of the Training of Elderly Caregivers within the training institutions in the health area of the state of Ceará. It is a research of an evaluative nature, of a diagnostic nature, with a qualitative approach to data analysis. Semi-structured interviews and documentary analysis were used as instruments for data collection. The subjects of the research were constituted by the teachers and coordinators belonging to the mentioned formations. It was verified that the training proposals for Elderly Caregivers investigated are supported in documents elaborated in different formats: Report and Political Pedagogical Project with organization of a curricular matrix referring to the private and public institution respectively. It was verified that the description, foundation and organization of the pedagogical proposals are more consolidated in the formative proposal of the public institution. Finally, the research culminated in the construction of a thematic matrix through the practical theoretical knowledge of the subjects, and the knowledge of the researcher's experience. Palavras-chave: Formação. Cuidadores de idosos. Matriz temática.